(untitled) (Journal of Engineering, 2024)
The most significant challenges wireless broadcasting systems face are channel effects and Inter Symbol Interference (ISI). Many different kinds of channel coding are employed to get around these issues. Digital Video Broadcasting for Satellite Telecommunication Second Generation (DVB-S2) uses a serial concatenation of Bose, Ray-Chaudhuri, and Hocquenghem (BCH) code and Low-Density Parity-Check (LDPC) code as a Forward Error Correction (FEC) for error detection purpose and correction. In this work, a MATLAB code (m-files) is constructed to simulate the standard DVB-S2 Bit-Interleaved Coded Modulation (BICM) system according to the ETSI Technical Report (EN 302 307 1). Then, the traditional design is redesigned with a Parallel Concatenation Convolutional (PCC) Turbo coding in concatenation with LDPC coding to enhance the (FEC). The two approaches have been tested under the official modulation types QPSK, 8PSK, 16APSK, and 32APSK with 2/3, 3/4, 3/5, 4/5, and 5/6 code rates (RC). Over a Rayleigh Fading channel, the two models are compared. The proposed model performed better than the standard model regarding bit error rate (BER) mitigation when operating at varying signal-to-noise ratio (SNR) levels, especially in 8PSK 3/5 MODCODE. The proposed model achieved (2.6272×10-3) BER mitigation value with power gain equal to 4 dB.